PENGELOLAAN PEMBELAJARAN DIKLAT BERBASIS MODEL TEAMS LEARNING TOURNAMENT - Firdos Mujahidin (Balai Diklat Keagamaan Bandung, 2018)
The background of this study is based on the still large amount of training learning that has not optimized the role of participants in the learning process while instilling and familiarizing attitudes. The purpose of this study is to describe the management strategy of training learning based on the Teams Learning Tournament (TLT) learning model. The method used in this study is the Pre-experimental method in the form of One-shot Case Study with the technique of collecting data through observing the results of giving action in learning. The results of the study show that the learning tournament-based training model management strategy is more effective in creating a fun learning process and fostering attitudes, especially discipline, responsibility and cooperation, so that the learning outcomes can be better. Because with the TLT model all training participants are required to show loyalty to their groups while producing quality group products, so that individual contributions are needed by the group. Groups formed can compete in a healthy manner. Keywords: training, education and training learning, Teams Laerning Tournament learning model, managing strategies.